A Katherine Mansfield Chronology - Norburn, R. author. aut Link
XVII, 146 p.
Keywords: This new addition to the Author Chronologies series details the tumultuous and tragic life of Katherine Mansfield (she died from tuberculosis aged only thirty-four) and sheds new light on her approach and attitudes to writing.